2013
DOI: 10.1262/jrd.2013-026
|View full text |Cite
|
Sign up to set email alerts
|

Treating Cloned Embryos, But Not Donor Cells, with 5-aza-2’-deoxycytidine Enhances the Developmental Competence of Porcine Cloned Embryos

Abstract: The efficiency of cloning by somatic cell nuclear transfer (SCNT) has remained low. In most cloned embryos, epigenetic reprogramming is incomplete, and usually the genome is hypermethylated. The DNA methylation inhibitor 5-aza-2’-deoxycytidine (5-aza-dC) could improve the developmental competence of cow, pig, cat and human SCNT embryos in previous studies. However, the parameters of 5-aza-dC treatment among species are different, and whether 5-aza-dC could enhance the developmental competence of porcine cloned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 31 publications
(44 reference statements)
1
60
0
Order By: Relevance
“…So it was great difficulty, if possible, to determine which genes were responsible for the improvement of embryonic development. It had been reported that regulating epigenetic status can improve the reprogramming efficiency both in SCNT and iPS (Kishigami et al 2006, Huangfu et al 2008, Onder et al 2012, Huan et al 2013, Matoba et al 2014. Therefore, we also examined the iPS efficiency after reducing H3K27me3 level.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…So it was great difficulty, if possible, to determine which genes were responsible for the improvement of embryonic development. It had been reported that regulating epigenetic status can improve the reprogramming efficiency both in SCNT and iPS (Kishigami et al 2006, Huangfu et al 2008, Onder et al 2012, Huan et al 2013, Matoba et al 2014. Therefore, we also examined the iPS efficiency after reducing H3K27me3 level.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, abnormal epigenetics reprogramming also often occur in these areas during iPS induction, and the reprogramming efficiency could be improved by regulating these epigenetic status both in SCNT and iPS (Kishigami et al 2006, Huangfu et al 2008, Onder et al 2012, Huan et al 2013, Matoba et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Increased blastocyst rates and OCT4, SOX2, NANOG expression when used in fetal fibroblast cells Huan et al, 2013 Buffalo somatic cells…”
Section: Histone Demethylating Strategiesmentioning
confidence: 99%
“…Successful cloning using mammalian somatic cell indicates that epigenetic modifications in the differentiated nucleus can be remodeled to a totipotent state [2]. The first living cloned piglet obtained by nuclear transfer of adult granulosa cells was reported in 2000 [4], and subsequently, additional porcine clones have been obtained [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Embryo aggregation consists of placing more than one zona free embryos in the same well; some of the reported benefits in mammals are: improvement in embryo development in pig [6], equine [8,9], feline [10] and mouse [11], increasing the density of cells in the inner cell mass on cattle [12], blastocyst diameter in equine and in bovine [8,13], reduction in apoptosis in bovine and pigs [13,14,15], normalization of gene expression in bovine [15]and in some cases, it has also improved in vivo embryo development and early pregnancy rates in mouse [11], equine [8] and in cattle [13,16,17]. As a single clone may have epigenetic defects [15], embryo aggregation could compensate the reprogramming deficiencies through the interactions between blastomeres [11] or by paracrine pathways [11].…”
Section: Introductionmentioning
confidence: 99%